Coupling Lagrangian simulation models and remote sensing to explore the environmental effect on larval growth rate: The Mediterranean case study of round sardinella (Sardinella aurita) early life stages - Torri, Marco; Russo, Stefania; Falcini, Federico; De Luca, Biagio; Colella, Simone; Volpe, Gianluca; Corrado, Raffaele; Placenti, Francesco; Giaramita, Luigi; Musco, Marianna; Masullo, Tiziana; Bennici, Carmelo; et al. (Frontiers in Marine Science, 2023)
The relationship between environmental conditions and early life-history traits of Sardinella aurita are investigated using material collected in two sites of the Central Mediterranean Sea. Individual mean daily growth during the planktonic phase has been determined by using otolith microstructure analysis, while Lagrangian simulation models allowed to estimate the daily position in space and time of each specimen from the hatching to the catch. Generalized Additive Mixed Models (GAMMs) have been implemented to explore the impact of environmental conditions at time t, t-1 day and t-2 days on the mean daily growth rate occurring at time t. Spatial analysis evidenced a wide dispersion of eggs and larvae in the coastal area of both sampling sites in correspondence to relatively warmer and chlorophyll-a enriched waters. Lagrangian simulations detected a complementary larval dispersal pathway able to transport larvae to a known retention area. Temperature at time t was the most important driver affecting the mean daily larval growth, followed by the food availability. On the other hand, models performed on lagged environmental covariates (t-1 and t-2) did not show any significant effect on the growth rate at time t, stressing the importance of co-occurring temperature and food availability conditions on growth patterns. In addition to the sub-linear positive correlation between temperature and mean daily larval growth, model highlighted a decrease in the otolith core width at higher temperature that can be linked to an earlier stage of ontogeny at hatching due to a reduced time for the egg development. This study provided a useful methodological approach that takes advantage of available remote sensing data to perform ecological studies in support to fisheries management.